INTEGRATING EXERCISE AND NUTRITION INTO AGED CARE TO REDUCE FRAILTY - Duque, G. (Innov Aging, 2017)
Frailty is a common clinical syndrome in older persons that has been associated with an increased risk for poor health outcomes including falls, incident disability, hospitalization, and mortality. Physical inactivity, vitamin D deficiency and poor nutrition accelerate the progression of frailty. Despite strong consensus on the importance of identifying and treating frailty, therapeutic choices for frailty are limited. In this presentation we will review the current state of knowledge about frailty and will analyze preventive measures and therapeutic interventions that can benefit both conditions simultaneously. We intend to go over the translational aspects of frailty research and highlight expected outcomes from different interventions for this condition. We will initially review the mechanisms contributing to frailty including metabolic and cell signalling changes. For example, we will analyze how changes in protein and amino acid intake as well as muscle wasting could be associated with frailty. Then, we will discuss evidence-based therapeutic interventions that pose promising opportunities for frailty focusing on nutritional interventions and physical activity. Finally we will translate this information into practical approaches that can improve care and decrease disability and poor outcomes in old frail individuals.